2017
DOI: 10.1371/journal.pone.0184535
|View full text |Cite
|
Sign up to set email alerts
|

Possible clinical effects of molecular hydrogen (H2) delivery during hemodialysis in chronic dialysis patients: Interim analysis in a 12 month observation

Abstract: Background and aimIt is supposed that enhanced oxidative stress and inflammation are involved with the poor clinical outcomes in patients on chronic dialysis treatment. Recent studies have shown that molecular hydrogen (H2) is biologically active as an anti-inflammatory agent. Thus, we developed a novel hemodialysis (E-HD) system which delivers H2 (30 to 80 ppb)-enriched dialysis solution, to conduct a prospective observational study (UMIN000004857) in order to compare the long-term outcomes between E-HD and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…For example, oxidized albumin can be reduced after the use of hydrogen‐containing blood dialysate, which can also relieve oxidative stress during hemodialysis and reduce the incidence of cardiovascular events. Therefore, hydrogen‐rich dialysate can reduce the occurrence of end‐point events and improve the prognosis of patients compared with conventional hemodialysis …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, oxidized albumin can be reduced after the use of hydrogen‐containing blood dialysate, which can also relieve oxidative stress during hemodialysis and reduce the incidence of cardiovascular events. Therefore, hydrogen‐rich dialysate can reduce the occurrence of end‐point events and improve the prognosis of patients compared with conventional hemodialysis …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hydrogen-rich dialysate can reduce the occurrence of end-point events and improve the prognosis of patients compared with conventional hemodialysis. 39,40 The hydrogen-containing peritoneal dialysate was first applied in rat model, and peritoneal fibrosis is effectively prevented after the administration of peritoneal dialysis. 20 There was a case report in which hydrogen-containing peritoneal dialysate and hemodialysis solution were applied for 63 days in an encapsulated peritoneal sclerosis (EPS) patient, and the peritoneal biopsy result showed that the intestinal cysts were not obvious.…”
Section: Discussionmentioning
confidence: 99%
“…Grades 3, 4 and 5 are regarded as fatigued states. We have already used this scale for the assessment of fatigue in two previous studies [14,15]. Although the effectiveness of this scale has not yet been validated, we used this scale because of its usability and lower cost than other scales.…”
Section: Assessments Of Fatigue and Depressionmentioning
confidence: 99%
“…Currently, there is no known pharmaceutical therapy that is able to improve blood perfusion in the ischemic limbs of patients with PAD ( 2 , 6 ). Hydrogen gas inhalation or hydrogen-saturated water has been widely used in a variety of clinical conditions, including strokes, and its efficacy and safety in patients has been demonstrated in previous studies ( 31 , 32 ). In line with these studies, the present study demonstrated that oral administration of H 2 was effective for the treatment of PAD, which is a convenient method for clinical use.…”
Section: Discussionmentioning
confidence: 99%